Perception, practices and understanding of teenage pregnancy among the adolescent girls in India: A scoping review protocol - Arpita Panda; Jayashree Parida; Susangita Jena; Abinash Pradhan; Sanghamitra Pati; Harpreet Kaur; Subhendu Kumar Acharya (Journal of Family Medicine and Primary Care, 2024)
Introduction: Teenage pregnancy is a subject of concern among adolescents. Inadequate knowledge and misperceptions about pregnancy are major contributing factors to teenage pregnancy. Without a proper understanding, adolescents are involved in unsafe sexual practices, which results in pregnancy. So, perception and understanding are important aspects to explore among adolescents. In this planned scope review, all eligible studies will be identified around the perception, practices, and understanding of teenage pregnancy among married and unmarried adolescent girls. Methods: The Arksey and O’Malley (2005) scoping review framework and the Joanna Briggs Institute Reviewers’ Manual (2015) will be used for the planned scoping review. The population, concept, and context strategy (PCC) will be used to develop the research question, search strategy, and eligibility criteria. Preferred Reporting Items for Systematic Review and Meta-Analysis Extension for Scoping Reviews (PRISMA ScR) will be used for the findings of the study. For the literature search, authors will use Google Scholar, PubMed, and ResearchGate electronic databases with specific words such as “teenage”, “adolescence”, “pregnancy”, “perception”, “knowledge”, “awareness” and “abortion”. Result: The planned scoping review will be helpful in addressing the lack of adolescent misperception, malpractices, and misunderstandings regarding teenage pregnancy. It can provide detailed information about teenage pregnancy in the Indian context. Conclusion: The evidence synthesis and gap analysis will be helpful in suggesting insights into the issue of teenage pregnancy, which will be helpful in future policies and programs.